A Multi-User Subcarrier Power Joint Allocation Algorithm Based on Rate Fairness - Jianwu Zhang; Lu Jin; Xiaorong Xu (Dianxin kexue)
With the rapid development of wireless communication technology，the demand for wireless resources increases quickly，and to improve the quality of service are required by users.Therefore，the intelligence is needed to carry out an effective compromise between user quality of service（QoS）requirements and wireless resource constraints in future communication systems.In order to enhance the spectral efficiency in cognitive radio network（CRN），multi-user subcarrier power joint allocation algorithm based on rate adaptive（RA）criterion in cognitive orthogonal frequency division multiplexing（OFDM）system was proposed in the constraint conditions of available subcarrier，secondary user（SU）power budget and rate fairness，with the consideration of rate fairness between SUs.This algorithm was separated into two steps with subcarrier and power allocation respectively.The proposed scheme could maximize link capacity with the consideration of the fairness among all SUs.Simulation results show that the joint allocation algorithm can get effective tradeoff between system throughput and the rate fairness of SU.